IN THE BEGINNING WAS THE ‘DIMENSIONS’. THEN, EVENING PASSED AND MORNING CAME - THE ‘SOCK’ IN DOCTORAL RESEARCH - Mammen, Asha Sara (International Journal of Research -GRANTHAALAYAH, 2020)
An evaluation and understanding of that genre of academic degree attributed as the highest academic recognition bestowed by a university - the PhD or the doctoral research programme, is the aim of this essay article. The attributes or nature of the doctoral programme are referred to by the writer as ‘dimensions’. The researcher utilized various reliable sources both offline and online and gathered information from seminars and talks of intellectuals from the academia in synthesizing information to create a piece of writing that comes from the prespective of an early research scholar. Research projects are done by way of a dissertation at all levels of higher education. The question asked is - can we carry the same mindset, structure and rigour of the research undertaken at the undergraduate level of education, or more precisely, the master’s research to the PhD research programme? And of course, can there be that confidence that one can bring or feel or have as a result, to the PhD programme? Furthermore, a question that is asked in the doctoral education programme is - whether a scholar creates or invents knowledge? Or is it the use of the philosophical frameworks of the science of knowledge, in attempting to bring out what is already there, to be justified and tested, thus classifying and giving it an orderly and labelled existence, which then becomes the new form of knowledge? Doctoral research projects undertaken are of various orientations, yet there is that element, a movement to the ‘SOCK’ which makes a PhD worthy. This research paper reviews and shares insights from the perspective of an early research scholar on the various premises and claims to make rationale the arguments/research questions stated.